Refractive and visual outcomes after Ferrara corneal ring segment implantation at a 60% depth in keratoconic eyes: case series - Renesto,Adimara da Candelaria (2019)
ABSTRACT Purpose: This report addresses refractive, topographic, visual acuity, and optical coherence tomography outcomes 12 months after femtosecond, laser-assisted insertion of Ferrara intrastromal corneal ring segments in keratoconic eyes at a depth of 60%. Methods: Interventional, prospective, non-comparative case series. We performed femtosecond, laser-assisted insertion of Ferrara intrastromal corneal ring segments in 15 keratoconic eyes. We included patients with documented keratoconus who voluntarily signed informed consents if they had best spectacle-corrected visual acuity ≥0.30 logMAR and corneal thickness ≥400 μm. We excluded patients with previous ocular surgery or corneal curvatures >65 diopters (D). Our main outcome measures were best spectacle-corrected visual acuity and corneal topographic parameters (flattest, steepest and average keratometry [K]), evaluated at baseline and at 1-,3-,6-, and 12-month follow-ups. Results: The mean ± standard deviation baseline uncorrected visual acuity and best spectacle-corrected visual acuity were 1.03 ± 0.46 and 0.42 ± 0.13, respectively; the 12-month mean standard deviation uncorrected visual acuity and best spectacle-corrected visual acuity were 0.72 ± 0.37 and 0.31 ± 0.16, respectively, without significant differences (p=0.05 for both). The mean best spectacle-corrected visual acuity improvements were statistically significant after 3- (p=0.02) and after 6-months (p=0.02). The mean baseline flattest (K1), steepest (K2), and overall keratometries (mean power) were 48.35 ± 3.65 D, 53.67 ± 3.38 D, and 50.84 ± 3.36 D, respectively. The 12-month mean ± standard deviations for flattest-K1, steepest-K2, and overall K were 46.53 ± 3.70 D, 49.83 ± 3.50 D, and 48.12 ± 3.49 D respectively, with statistically significant differences for all three topographic parameters (p=0.01). Conclusions: Ferrara intrastromal corneal ring segment insertions at a depth of 60% yield satisfactory visual, refractive, and keratometric results in keratoconic eyes.